An endeavour to animate and incourage our soldiers, for the present expedition : made, and fitted to the tune of George's coronation - M. B., active 1758 (Printed and sold by Green and Russell, in Queen-Street, 1758)
1758? Song by M.B., entitled " An Endeavour to animate and incourage our Soldiers, for the present Expedition," which was made and fitted to the tune of George's Coronation. Of note, the tune was in support of the British troops against the French and had numerous anti-Catholic references.